Original paperInvasive treatment for carotid fibromuscular dysplasia - Tekieli, Łukasz M.; Maciejewski, Damian; Dzierwa, Karolina; Kabłak-Ziembicka, Anna; Michalski, Michał; Wójcik-Pędziwiatr, Magdalena; Brzychczy, Andrzej; Moczulski, Zbigniew; Żmudka, Krzysztof; Pieniążek, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: Fibromuscular dysplasia (FMD) is an infrequent non-inflamatory disease of unknown etiology that affects mainly medium-size arteries. The prevalence of FMD among patients scheduled for endovascular treatment of carotid artery stenosis is unknown. Aim: To evaluate the prevalence and treatment options of carotid FMD in patients scheduled for carotid artery stenting (CAS). Material and methods: Between Jan 2001 and Dec 2013, 2012 CAS procedures were performed in 1809 patients (66.1% men; age 65.3 ±8.4 years, 49.2% symptomatic). In case of FMD suspicion in Doppler-duplex ultrasound (DUS), computed tomography angiography was performed for aortic arch and extracranial and intracranial artery imaging. For invasive treatment of FMD carotid stenosis, balloon angioplasty was considered first. If the result of balloon angioplasty was not satisfactory (> 30% residual stenosis, dissection), stent placement was scheduled. All patients underwent follow-up DUS and neurological examination 3, 6 and 12 months after angioplasty, then annually. Results: There were 7 (0.4%) (4 symptomatic) cases of FMD. The FMD group was younger (47.9 ±7.5 years vs. 67.2 ±8.9 years, p = 0.0001), with higher prevalence of women (71.4% vs. 32.7%, p = 0.0422), a higher rate of dissected lesions (57.1% vs. 4.6%, p = 0.0002) and less severe stenosis (73.4% vs. 83.9%, p = 0.0070) as compared to the non-FMD group. In the non-FMD group the prevalence of coronary artery disease was higher (65.1% vs. 14.3% in FMD group, p = 0.009). All FMD patients underwent successful carotid artery angioplasty with the use of neuroprotection devices. In 4 cases angioplasty was supported by stent implantation. Conclusions: Fibromuscular dysplasia is rare among patients referred for CAS. In case of significant FMD carotid stenosis, it may be treated with balloon angioplasty (stent supported if necessary) with optimal immediate and long-term results.